Capacity of liquid-filled steel conical tanks under vertical excitation. (June 2016) - Musa, Ahmed; El Damatty, Ashraf A.
Abstract: Liquid tanks in the form of truncated cones are commonly used for liquid storage in North America and in other locations. This paper is a part of an extensive research program aimed to develop a comprehensive design procedure for liquid-filled steel conical tanks under seismic loading. Because of the inclination of the walls of conical tanks, the vertical component of the ground motion excitation has a significant effect on conical tanks compared to the case of cylindrical tanks. To the best of the authors' knowledge, the current study is the first to focus on the assessment of the capacity of steel conical tanks under the vertical component of a seismic excitation. The study is carried out numerically using an in-house finite element model by conducting nonlinear static pushover analysis under a load distribution simulating hydrodynamic pressure associated with vertical ground excitations. The numerical model accounts for the effects of geometric and material nonlinearities as well as initial geometric imperfections. Charts are developed to estimate the capacity of steel conical tanks to resist vertical ground excitations based on yielding and buckling criteria for different imperfection levels. The developed charts are used to estimate the capacities of a number of steel conical tanks which are then compared to the hydrodynamic loading associated with various seismic zones. Highlights: Evaluating capacity of steel conical tanks subjected to vertical excitations. Studying the effect of geometric imperfections on the capacity of steel conical tanks. Comparing the tank capacities to the seismic demands for different seismic zones.